2016
DOI: 10.1016/j.jcms.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Inferior alveolar nerve function after open reduction and internal fixation of mandibular fractures

Abstract: a b s t r a c tPurpose: Mandibular fractures are amongst the most common facial fractures and are usually treated by open reduction and internal fixation (ORIF). Inferior alveolar nerve (IAN) injuries are seen frequently in mandibular fractures as well as after ORIF of these fractures due to the exposition and the close proximity of the nerve during fracture reduction. Therefore the continuity of the IAN can be disrupted. Permanent injury to the IAN can result in diminished quality of life. This retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…Boffano et al in 2014 (23) reported a 24.3%. A retrospective study done by Schenkel and Jacobsen in 2016 (24) reported that one-third of the population suffered from postoperative paraesthesia, however with a 70% of the affected cases returning to normal. Owing to the slow neural regeneration, extending the follow up period of Schenkel and Jacobsen study might have yielded in a 100% recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Boffano et al in 2014 (23) reported a 24.3%. A retrospective study done by Schenkel and Jacobsen in 2016 (24) reported that one-third of the population suffered from postoperative paraesthesia, however with a 70% of the affected cases returning to normal. Owing to the slow neural regeneration, extending the follow up period of Schenkel and Jacobsen study might have yielded in a 100% recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Fraktür tamir tipi de nöropati oluşumunda etkili bir faktördür. Mandibula fraktürlerinin açık redüksiyonu sonrası kapalı redüksiyona kıyasla daha yüksek oranda uzun süreli nöropati oluştuğu rapor edilmiştir [17][18][19][20][21] .…”
Section: Hasar Nedenleri̇ 1 Fasiyal Travmaunclassified
“…Anterior mandibular fractures (AMFs) are defined as fractures that occur in the region between the lateral incisor and the second premolar (parasymphyseal region), or fractures that occur in the region between the lateral incisors (symphyseal region). 1 Although there is a wide variance in the recorded percentage of mandibular fractures that occur in the anterior region, the aggregate analysis places them at approximately 17% of all mandibular fractures. 2,3 Various types of plating systems have been evolved during the past decades to provide a stable anatomic reduction for AMFs, so the risk of the postoperative displacement of the fractured segments could be reduced and the early return to normal function is allowed.…”
Section: Introductionmentioning
confidence: 99%